2015
DOI: 10.2967/jnumed.114.153031
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Simplified Blood Dose Protocols for the Estimation of the Maximum Tolerable Activity in Thyroid Cancer Patients Undergoing Radioiodine Therapy Using 124I

Abstract: In high-activity radioiodine therapies for differentiated thyroid cancer, blood dosimetry has been developed to estimate the maximum tolerable activity (MTA) of 131 I that can be safely administered without leading to toxic effects. The reference protocol involves a series of both blood sampling (BS) and whole-body counting (WC) over a period of several days. The aim of this retrospective study was to identify simplified protocols without an appreciable loss of accuracy. Methods: Data from 211 thyroid cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
1
23
1
Order By: Relevance
“…The individual calculated MTAs at MSKCC were not reported (1), but the AAs were lower than in our experience (4). This raises concern that AAs differ from calculated MTAs.…”
contrasting
confidence: 38%
“…The individual calculated MTAs at MSKCC were not reported (1), but the AAs were lower than in our experience (4). This raises concern that AAs differ from calculated MTAs.…”
contrasting
confidence: 38%
“…In contrast, we perform an individual pretherapy dosimetry for high-risk patients using the positronemitting tracer 124 I-NaI ( 124 I). In this dosimetry approach, the lesion-absorbed radiation dose (AD) per unit of 131 I activity is estimated using 124 I PET/CT and the maximum tolerable activity is derived from blood sample and whole-body retention data (3,4). The maximum tolerable activity is defined as the maximum therapeutic activity that can be administered without producing severe bone marrow or lung toxicities ($grade 3 according to the National Cancer Institute Common Terminology Criteria for Adverse Events, version 4.0).…”
mentioning
confidence: 99%
“…It helps to measure (average) absorbed doses of 131 I to organs of interest, enabling quantitative dose-response studies, dose planning before therapy, dose evaluation during therapy and further investigations of the ''stunning'' phenomenon [27][28][29][30][31]. On the basis of a theoretical dosimetry based model using 124 I, Jentzen et al, showed that the lowest effective therapy activity required for thyroid remnant ablation in low risk differentiated thyroid cancer appears to be approximately 2.2 GBq [32].…”
Section: Applications 124 I In Thyroid Diseasementioning
confidence: 99%